2022
DOI: 10.1177/20494637221091474
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a quality improvement project on post-operative opioid use following outpatient spinal surgery

Abstract: Background: Prescribing opioids upon discharge after surgery is common practice; however, there are many inherent risks including dependency, diversion, and medical complications. Our prospective pre- and post-intervention study investigates the effect of a standardized analgesic prescription on the quantity of opioids prescribed and patients' level of pain and satisfaction with pain control in the early post-operative period. Methods: With the implementation of an electronic medical record, a standardized pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Magnan et al 17 previously demonstrated that a combined intervention of standardized prescriptions and preoperative education handouts were effective in reducing oral morphine equivalents in an adult population undergoing elective spinal surgery. Furthermore, a systematic review by Rucinski et al 18 demonstrated the effectiveness of preoperative education related to opioid use and pain at reducing opioid prescription requests and filling.…”
Section: Discussionmentioning
confidence: 99%
“…Magnan et al 17 previously demonstrated that a combined intervention of standardized prescriptions and preoperative education handouts were effective in reducing oral morphine equivalents in an adult population undergoing elective spinal surgery. Furthermore, a systematic review by Rucinski et al 18 demonstrated the effectiveness of preoperative education related to opioid use and pain at reducing opioid prescription requests and filling.…”
Section: Discussionmentioning
confidence: 99%
“…Two papers in this issue of the British Journal of Pain focus on improvements in pre- and post-operative care, both of which can contribute to improved outcomes and reduced medicines use. 7,8 Such initiatives can form part of an analgesic stewardship strategy for health care organisations, which includes not just pain services but colleagues from a range of professional groups, each with their own role to play.…”
mentioning
confidence: 99%